Concept of chivalry (futuwwah) according to Abd Al-Razzaq Kashani : analysis on his Tuhfah Al-Ikhwan Fi Khasais Al-Fityan / Fatemeh Tayefeh Aghakhan Hashtroodi - Hashtroodi, Fatemeh Tayefeh Aghakhan (2015)
The purpose of this topic of study is to examine the esoteric meaning of chivalry (futuwwah) by Kāshānī, based on the grounds of the School of Wahdah al-Wujūd, and to describe the theoretical classification of moral specification of chivalry. This study will open up a relatively unexplored aspect of chivalry, that reflects the concept of the mediocre imperfect human being, the lower level of the perfect human as identified by Sufis. The library research, collecting and analyzing data primary and secondary sources, makes it possible to draw a clear image of Kāshānī’s School of thought. Indeed, the combined historical and religious approach of chivalry clarifies improvement of the primary concept of chivalry within Qur’ānic teaching, and its appearance as the ethical code in different dimensions of a Muslim’s life such as public, politics and economy. A comparative study of chivalry letters from the twelfth to sixteenth century depicts continued development of the concept of chivalry within Sufism. It reveals the concept of chivalry has improved from its primordial concept as forgiveness into the spiritual school of thought, with theoretical and practical dimensions attached to the individual and social life of humans. And, it is finally integrated to the spiritual stage of Sufism as benefaction. The theoretical dimension of chivalry is developed on the grounds of School of Wahdah al-Wujūd by Kāshānī, which presents the integration of the concept of chivalry with unity, love and justice. Chivalry is identified as the stage of appearance of the knowledge of Unity ( d), which implies the knowledge of self awareness, through which man perceives his true nature, his dignity and potentialities. The analytical perspective of chivalry portrays a figure of human being in terms of a human being, whose journey of life begins with returning to his real being, to a greater degree of actualizing his potentialities bestowed to him by God. It is a continuous challenge of a human being, with all his imperfections and faults, to express God’s love to His creation in order to satisfy Him and bring happiness in human life.